The Effectiveness of Intraoperative Ketamine and Fentanyl as Preemptive Analgesia Assessed with qNOX Score - Wilesing Gumelar; Hamzah Hamzah; Christijogo Sumartono (Perhimpunan Dokter Spesialis Anestesiologi dan Terapi Intensif, 2021)
Background: Inadequate management of intraoperative pain poses a risk of postoperative chronic pain complications. The use of preemptive analgesia before the onset of surgical incision stimulation was considered to prevent central sensitization. Clinical research around the terms of preemptive analgesia needs to be proven by nociception-based intraoperative monitoring. An objective modality with EEG guidance can provide information on noxious stimuli.Objective: To determine the effectiveness of ketamine and fentanyl administration as preemptive analgesia measured by qNOX scores through the CONOX tool.Methods: This study is a single-blinded randomized experiment with the division of two groups: control and treatment. The control group received preemptive fentanyl, and the treatment group received preemptive ketamine and fentanyl. Then the qNOX score was assessed during operation.Result: The qNOX score of the treatment group in minute-15 and 30 was lower than the control group (p = 0.007; p = 0.025), while in the minute-90 it was higher than the control group (p = 0.001). The mean first 1-hour qNOX score was lower in the treatment group (p <0.001), while in the second 1-hour was higher in the treatment group (p = 0.003). The mean total dose of fentanyl supplementation in the treatment group was lower than in the control group (71.3 ± 25.1 grams vs. 92.0 ± 28.3 grams; p = 0.044).Conclusion: The administration of combined ketamine and fentanyl as preemptive analgesia is more effective in the first hour of surgery compared to single preemptive fentanyl measured by qNOX score. Preemptive ketamine and fentanyl decrease the total dose of intraoperative fentanyl supplementation compared with single-dose preemptive fentanyl administration.